Decentralization in Regional Fiscal Systems in Russia : Trends and Links to Economic Performance - Frejnkman, Lev M. (The World Bank, 1999)
April 1999 - Considering the positive impact decentralization has had on regional economic performance and expenditure structure, Russia's federal government should: ° Decisively protect local self-governance and budget autonomy. ° Make intergovernmental fiscal relations more transparent. ° Develop universal models of interactions between regional and municipal governments. ° Impose stricter limits on total debt and budget deficits of subnational governments. To shed light on decentralization in Russia, Freinkman and Yossifov examine intergovernmental fiscal relations within regions. To analyze trends, they review channels of fiscal allocation within regions-tax sharing and local transfer schemes. To evaluate the potential impact of various fiscal decentralization patterns on regional economic performance (including growth and the budget deficit), they study data on the structure of 89 Russian consolidated regional budgets for 1992-96. They find that local governments' relative share of Russia's consolidated budget, although substantive (roughly a quarter of the total budget), did not expand after 1994. The federal government's relative role in financing public goods and services declined as the relative role of local governments increased substantially. Local governments collected more revenues in 1996 (6.4 percent of GDP) and spent more than regional governments. They also substantially increased social financing (including health, education, and social protection). Russia made no progress toward a more transparent system for tax assignments. The average level of expenditure decentralization is similar for ethnically Russian regions and national republics and okrugs but revenue arrangements differ greatly. True decentralization has taken place in oblasts and krais, where local authorities are provided with a bigger share of subnational tax revenues.